2018
DOI: 10.1016/j.aquaculture.2018.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of cryopreserved black-lip pearl oyster Pinctada margaritifera spermatozoa

Abstract: High quality of sperm is essential to a high fertilization rate, especially post-cryopreservation. Assessment of sperm integrity, motility and energy reserves before cryopreservation is necessary for selection of milt with optimal fertilizing potential. We describe the effect of cryopreservation on the quality of black-lip pearl oyster, Pinctada margaritifera var. cumingii sperm. Evaluated quality indices of fresh and frozen/thawed P. margaritifera spermatozoa, included morphology, ultrastructure and motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The ATP levels in sperm during peak breeding seasons and in different cryopreserved sperm showed a trend of variation similar to that observed for sperm motility and mRNA expression of Hdh-TEKT4 in the same sperm sample. It has been reported that the motility and ATP content of oyster sperm can be significantly affected by the freeze–thaw process of cryopreservation ( Demoy-Schneider et al, 2018 ). A significant decrease in the ATP content in the cryopreserved sperm of Pacific oyster than in fresh sperm has been reported ( Suquet et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ATP levels in sperm during peak breeding seasons and in different cryopreserved sperm showed a trend of variation similar to that observed for sperm motility and mRNA expression of Hdh-TEKT4 in the same sperm sample. It has been reported that the motility and ATP content of oyster sperm can be significantly affected by the freeze–thaw process of cryopreservation ( Demoy-Schneider et al, 2018 ). A significant decrease in the ATP content in the cryopreserved sperm of Pacific oyster than in fresh sperm has been reported ( Suquet et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect of sugars in post-thaw sperm was also reported for several species such as boar, Salmonidae fish, and Australian flat oyster ( Gómez-Fernández et al, 2012 ; Nynca et al, 2016 ; Hassan et al, 2017a ). Trehalose and sucrose have shown an important role as supplement of the freezing medium during cryopreservation of bivalves, being mainly applied in larvae ( Choi et al, 2008 ; Labbé et al, 2018 ) and less in sperm ( Hassan et al, 2017a ; Demoy-Schneider et al, 2018 ). Moreover, studies in bivalve sperm were performed with a low number of quality analyses both in the fresh and post-thaw samples, being these analyses focused mainly on sperm motility, plasma membrane integrity, and fertilization success ( Vitiello et al, 2011 ; Horváth et al, 2012 ; Suquet et al, 2016 ; Hassan et al, 2017a , b ), thus lacking important information on sublethal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mollusc sperm biological characteristics, cryopreservation and quality assessment have become more numerous since reviewed by Gwo (Gwo, ; Hassan, Qin, & Li, ). These studies concerned oyster species (Boulais et al, ; Suquet et al, ; Suquet, Rimond, et al, ), pearl oyster species (Demoy‐Schneider, Levêque, Schmitt, Le Pennec, & Cosson, ; Demoy‐Schneider, Schmitt, Le Pennec, Suquet, & Cosson, ; Zheng et al, ) and so on. However, studies for scallop species were limited to Pecten maximus (Suquet, Arsenault‐Pernet, Ratiskol, & Mingant, ; Suquet, Gourtay, et al, ; Suquet, Malo, et al, ; Suquet, Quéré, et al, ), Argopecten purpuratus (Lamarck, 1819) (Dupré, Covarrubias, Goldstein, Guerrero, & Rojas, ; Espinoza, Valdivia, & Dupre, ), Chlamys farreri (Li, Li & Xue, 2000; Xue, ) and Patinopecten yessoensis (Yang et al, ; Yang, Yang, Liu, & Zhou, , ).…”
Section: Introductionmentioning
confidence: 99%